2016
DOI: 10.3892/ol.2016.4633
|View full text |Cite
|
Sign up to set email alerts
|

Protection of organs at risk during neoadjuvant chemoradiotherapy for gastric cancer based on a comparison between conformal and intensity-modulated radiation therapy

Abstract: Abstract. The aim of the present study was to compare the techniques of dynamic intensity-modulated radiation therapy (IMRT) and three-dimensional conformal radiotherapy (3DCRT) in patients with gastric cancer. Implementation of the IMRT technique does not significantly affect the minimum and maximum dose levels in the planning target volume (PTV), but more effectively protects the critical organs. The study group consisted of 25 patients. The results of the analysis of the conformity index (CI) and the homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
6
1
1
Order By: Relevance
“…The radiation dose distribution can be improved in targeted areas while reducing the radiation dose in normal organs in IMRT (Ringash et al, 2005). Although IMRT provides superior treatment tolerance and reduces the risk of damage to healthy tissues, its advantageous effects on survival have not been reported in the literature (Hawrylewicz et al, 2016). In the present study, although the number of patients in stage IIIC were higher in the TOMO treated group, the survival rate was significantly better in those treated with TOMO.…”
Section: Discussioncontrasting
confidence: 49%
“…The radiation dose distribution can be improved in targeted areas while reducing the radiation dose in normal organs in IMRT (Ringash et al, 2005). Although IMRT provides superior treatment tolerance and reduces the risk of damage to healthy tissues, its advantageous effects on survival have not been reported in the literature (Hawrylewicz et al, 2016). In the present study, although the number of patients in stage IIIC were higher in the TOMO treated group, the survival rate was significantly better in those treated with TOMO.…”
Section: Discussioncontrasting
confidence: 49%
“…A previous study showed significant grade 3 toxicity in patients with resected gastric or gastroesophageal junction cancers treated with 3D-planned CRT [20]. In recent years, several clinical trials have been performed to evaluate clinical outcomes and toxicity in patients with resected gastric cancer treated with IMRT versus 3D-CRT [2128]. Minn et al [29] compared the clinical efficacy and adverse events in patients with gastric cancer who received IMRT versus 3D-CRT.…”
Section: Introductionmentioning
confidence: 99%
“…Die Chemotherapie parallel zur Bestrahlung ist zumeist platinbasiert und orientiert sich an den etablierten Standard-Protokollen der S3-Leitlinie Ösophagus-Karzinom in der jeweils aktuell gültigen Version, derzeit Version 1.0 -September 2015 AWMF-Register-Nummer: 021/023OL[524]. Aufgrund der sehr komplexen anatomischen Verhältnisse und der Lagevariabilität der Organe sind moderne Bestrahlungsverfahren wie intensitätsmodulierte Radiotherapie IMRT und Nachfolgetechniken (VMAT, volumenmodulierte Arc-Therapie) in Kombination mit einer bildgeführten Bestrahlung (IGRT, Image-guided Radiotherapy) und eine Bestrahlungsplanung in 4D-Technik zu bevorzugen, da sie eine bessere Schonung benachbarter Organe und eine sicherere Erfassung der zu behandelnden Region ermöglichen[524,[527][528][529][530]. Die Dosierung der Strahlentherapie erfolgt ebenfalls analog zur definitiven Radiochemotherapie des Ösophaguskarzinoms.11.…”
unclassified